E-office transaction system / Siti Najiha Yunos - Siti Najiha, Yunos (2004)
Accounting Information Systems is one of the critical systems in a corporation. This system will support all the critical financial information, which will be needed by the management in order to help them in their decision-making. Traditional accounting, which is manually written with a pen on the paper, has proven to be tedious job. Accountant needs to be very careful in order not to make any mistake while recording the transaction committed by the company. Therefore, computer-based accounting is being introduced in order to help the accountants manage their accounting set effectively. This new accounting systems ha helped to reduce mo t of the human-error and providing informative reports in a very short time. Web-based accounting system which will be develop in this project to provide an easy access through the internet for the users to gain their critical financial information. In this documentation development issues such as system requirements, methodology and system design in will discussed thoroughly. In the end of this documentation, several pre-develop interface ha been shown to provide an easy understanding of how this systems will look like.